Spousal Support During the Psychological Adaptation Process in Mothers Postpartum Period in the Jatiluhur Health Center Area - Hermina, Ine; Rahayu, Sopiawati Putri (Green Publisher Indonesia, 2025)
The postpartum period is a transitional period marked by various physical and psychological changes in mothers. Spousal support is one of the important factors influencing the success of the psychological adaptation process in postpartum mothers. This study aims to determine the relationship between the level of spousal support and the psychological adaptation process in postpartum mothers in the working area of the Jatiluhur Community Health Center. The research method used a descriptive correlational approach with a cross-sectional design on 80 postpartum mothers selected using purposive sampling. Data were collected using a spousal support questionnaire and a psychological adaptation questionnaire. The analysis results showed a significant relationship between spousal support and the psychological adaptation of postpartum mothers (p < 0.05). In conclusion, the higher the level of spousal support, the better the psychological adaptation of postpartum mothers. Education is needed for husbands regarding the importance of their role during the postpartum period to support the mental health of mothers.